Pengaruh Kualitas Fungsional Dan Kualitas Teknikal Terhadap Kepuasaan Mahasiswa Peserta Pelatihan Kepabeanan Tahun 2018 - Vivid Dekanawati; Supartini Supartini (Sekolah Tinggi Maritim Yogyakarta, 2019)
This study aims to find out: functional quality, namely caring, hospitality and professionalism. Technical quality with indicators, namely the determination of time, service speed and neatness of results, so that trainees can assess service after the respondent in question conducts customs training at the Yogyakarta Maritime Academy (AMY). The population in this study were all AMY semester V cadets as customs training participants. The samples taken in this study were students or so-called cadets who had attended 2018 customs training in a number of 125 participants. Census sampling technique. In this study the author uses a multiple linear regression analysis method, which is an analysis of the influence of more than one independent variable (X) on the dependent variable (Y). Data analysis in this study used the help of SPPS version 17.0 and to test hypotheses using multiple linear regression. The results of this study based on the results of the F test show the variables of functional quality and technical quality have a simultaneous influence on the satisfaction of participants. The results of the t test for technical quality variables have no significant effect on participant satisfaction. The test results of the coefficient of determination are jointly influenced by other variables besides functional quality and technical quality. Based on the results of the analysis of the stepwise method Functional quality has the most dominant effect on participant satisfaction